1991
DOI: 10.1210/endo-128-1-341
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity and Metabolic Clearance of a Recombinant Human Thyrotropin Produced in Chinese Hamster Ovary Cells

Abstract: The presence and specific structures of the oligosaccharides on TSH have been shown to be important for its production and bioactivity. Since the carbohydrate structure of a protein reflects the glycosylation apparatus of the host cells in which the protein is expressed, we examined the biological activity and metabolic clearance of a preparation of purified recombinant human (rh) TSH derived from a stable transfectant of Chinese hamster ovary cells. Carbohydrate compositional analysis of this rTSH showed it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 31 publications
0
53
1
3
Order By: Relevance
“…(1991) demonstrated that rhTSH is able to activate the TSH receptor, as reflected by the accumulation of cAMP, the induction of Tg secretion and thyroid epithelial cell multiplication. Although rhTSH has an amino acid structure identical to hTSH (Cole et al ., 1993), its glycosylation is different with higher sialic acid content (Thotakura et al ., 1991;Szkudlinski et al ., 1993). As a consequence, rhTSH exhibits lower immunological activity, lower TSH receptor binding affinity, and lower in vitro bioactivity than hTSH.…”
Section: Structural and Physiological Properties Of Rhtshbasic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1991) demonstrated that rhTSH is able to activate the TSH receptor, as reflected by the accumulation of cAMP, the induction of Tg secretion and thyroid epithelial cell multiplication. Although rhTSH has an amino acid structure identical to hTSH (Cole et al ., 1993), its glycosylation is different with higher sialic acid content (Thotakura et al ., 1991;Szkudlinski et al ., 1993). As a consequence, rhTSH exhibits lower immunological activity, lower TSH receptor binding affinity, and lower in vitro bioactivity than hTSH.…”
Section: Structural and Physiological Properties Of Rhtshbasic Aspectsmentioning
confidence: 99%
“…As a consequence, rhTSH exhibits lower immunological activity, lower TSH receptor binding affinity, and lower in vitro bioactivity than hTSH. The metabolic clearance rate (MCR) is significantly lower for rhTSH than for hTSH (Thotakura et al ., 1991) and due to this difference in MCR it may turn out that rhTSH in vivo is equivalent to or maybe more potent than hTSH, despite the lower in vitro bioactivity (Thotakura et al ., 1991). Estimated by immunoassays the specific activity of rhTSH is between 5·51 and 7·63 IU/mg based on the second International Reference Preparation (80/558) of hTSH as the standard (Rafferty & Gaines, 1999).…”
Section: Structural and Physiological Properties Of Rhtshbasic Aspectsmentioning
confidence: 99%
“…Once the b-subunit of the human TSH gene had been cloned (11), the encoded protein could be overexpressed in a cell system (Chinese hamster ovary cells), by transfection with the human a-and bsubunits of complementary or genomic DNA. With this technique, large quantities of highly puri®ed rhTSH can be obtained (12). Its bioactivity and metabolic clearance seem to be affected by the pattern of posttranslational glycosylation.…”
Section: Production Of Recombinant Human Tshmentioning
confidence: 99%
“…The Asn 52/56 oligosaccharide masks the secondary role of Asn 13 requiring that the former be eliminated before the impact of the latter can be demonstrated (Matzuk et al 1989). The subunit oligosaccharides exert their primary influence on hormone activity by determining the circulatory half-life of glycoprotein hormones (Rosa et al 1984, Bishop et al 1995, which is an important factor determining in vivo biological activity (Thotakura et al 1991).…”
Section: Introductionmentioning
confidence: 99%